False lumen enhancement characteristics on computed tomography angiography predict risk of aneurysm formation in acute type B aortic dissection. (8th May 2021) - Roseland, Molly E; Ahmed, Yunus; van Herwaarden, Joost A; Moll, Frans L; Yang, Bo; Patel, Himanshu J; Burris, Nicholas S
Abstract:  : OBJECTIVES: Differential luminal enhancement [between true lumen (TL) and false lumen (FL)] results from differential flow patterns, most likely due to outflow restriction in the FL. We aimed to assess the impact of differential luminal enhancement at baseline computed tomography angiography on the risk of adverse events in patients with acute type B aortic dissection (TBAD). METHODS: Baseline computed tomography angiographies of patients with acute TBAD between 2007 and 2016 ( n  = 48) were analysed using three-dimensional software at multiple sites along the descending thoraco-abdominal aorta. At each location, we measured contrast density in TL and FL [Houndsfield unit (HU)], maximal diameter (cm) and circumferential FL extent (°). Outcome data were collected via retrospective chart review. Multivariable logistic regression models were employed to determine the independent risk of TL–FL differential luminal enhancement on aneurysm formation (maximal diameter ≥55 mm) and medical treatment failure. RESULTS: Patients were predominately male (75%) and 52.8±12.9 years at diagnosis. The mean follow-up was 5.9±2.6 years, and 42% ( n  = 20/48) patients were diagnosed with thoraco-abdominal aortic aneurysm. The baseline absolute difference between FL and TL contrast density measured at 2 cm distal to primary entry tear (TL–FLabs-Tear ) was significantly higher among patients who developed aneurysm (26 HU, IQR: 15–53 vs 13 HU, IQR: 4–24, P  = 0.001). Aneurysm development during follow-up was predicted by TL–FLabs-Tear (odds ratio 1.07, P  = 0.012) and baseline maximal aortic diameter (odds ratio 1.90, P  < 0.001). High (≥18 HU) differential luminal enhancement was associated with lower rates of aneurysm-free survival and higher rates of medical treatment failure. CONCLUSIONS: Differential luminal enhancement may be a novel predictor of aneurysm formation among patients with acute TBAD.